Teaching NeuroImage: Cerebral Amyloid Angiopathy–Related Inflammation: An Interesting Evolution of Imaging Findings. (2nd August 2022) - Dudley, Alex; Sweeney, Kieron; Looby, Seamus; Farrell, Michael; McGovern, Eavan
Abstract : A 77-year-old previously well woman presented with confusion, visual hallucinations, and signs of parietal lobe dysfunction, preceded by 5 days of headache. MRI of the brain demonstrated diffuse sulcal fluid-attenuated inversion recovery hyperintensities (Figure, A) and subtle leptomeningeal enhancement. Susceptibility-weighted imaging (SWI) was normal (Figure, B). Neurosurgical biopsy-confirmed cerebral amyloid angiopathy with perivascular inflammation (Figure, D–F). Pulsed methylprednisolone was given with excellent clinical response. MRI 7 weeks post symptom onset demonstrated widespread microhaemorrhages (Figure, C).